Repressed Female Bodies in Contemporary Feminist Dystopias: Leni Zumas' Red Clocks and Sophie Mackintosh's Blue Ticket - ÖZBOLAT, MERVE GÜLER (İstanbul Kültür Üniversitesi, 2024)
This thesis investigates repressed female bodies and mechanisms that operate on them in contemporary feminist dystopian fiction analysing Red Clocks (2018) by Leni Zumas and Blue Ticket (2020) by Sophie Mackintosh. Through a comparative analysis of these two novels the common strategies, normalisation, the use of laws on the reproductive rights, and panoptic discipline as exercised by medical institutions and practices, employed by the patriarchal hegemonic structures to oppress female bodies, are discussed. To demonstrate the idea behind the oppression on female bodies this thesis revisits Western traditional mind and body dualism and the operation of power in repression. Referring to feminist theories of Elizabeth Grosz, Helene Cixous, Luce Irigaray the relationship between body and patriarchal power is discussed. Also, the works of Michel Foucault and Foucauldian feminists Jana Sawicki and Sandra Barkty are employed to analyse biopower, medical gaze and panoptic discipline on female bodies. In the light of these theories this study concludes that in both 21st century feminist dystopian novels Red Clocks and Blue Ticket female bodies are subjugated using similar strategies and, in both novels, dystopic worlds of women are not far from the real one that they experience.
Çağdaş Feminist Distopyalarda Bastırılmış Kadın Bedenleri: Leni Zumas'ın Kırmızı Saatler'i ve Sophie Mackintosh'un Mavi Bilet'i
Yüksek lisans tezi.
Keywords: Feminist Dystopia; Body; Biopower; Medical Gaze; Leni Zumas; Red Clocks; Sophie Mackintosh; Blue Ticket